The Effect of CSR, Intellectual Capital and GCG on Company Value with Financial Performance as a Moderating Variable in Food & Beverage Industry Companies Listed on the Indonesia Stock Exchange (IDX) - Andi Tenri Harahap; Andi Ratna Sari Dewi (Jurnal Economic Resource, 2023)
This study aims to examine the effect of Corporate Social Responsibility (CSR), Intellectual Capital and Good Corporate Governance (GCG) on company value with financial performance as a moderating variable in food and beverage industry companies listed on the IDX. This research is quantitative research, using secondary data obtained from the Indonesia Stock Exchange (IDX). The total population in this study is 54 companies listed on the Indonesia Stock Exchange in 2017 -2019. There are 11 companies that meet the criteria to be sampled in this company. The analysis technique used in this research is Descriptive Statistics test, Classical Assumption test, Multiple Linear Regression analysis, Hypothesis testing and MRA. The results of this study indicate that the CSR and Intellectual Capital variables have no significant effect on firm value, Good Corporate Governance and Financial Performance have a positive and significant effect on firm value. Indirectly, financial performance has succeeded in strengthening the relationship between CSR and Intellectual Capital on company value, while financial performance has not been able to moderate the relationship between Good Corporate Governance and company value.